Understanding meteorological and physio-geographical controls of variability of flood event classes in headstream catchments of China - Y. Zhang; Y. Zhang; X. Zhai; J. Xia; J. Xia; Q. Tang; W. Wang; J. Wu; X. Niu; B. Han (Hydrology and Earth System Sciences)
Classification is beneficial for understanding flood variabilities and their formation mechanisms from massive flood event samples for both flood scientific research and management purposes. Our study investigates comprehensive manageable flood event classes from 1446 unregulated flood events in 68 headstream catchments of China using hierarchical and partitional clustering methods. Control mechanisms of meteorological and physio-geographical factors (e.g., meteorology or land cover and catchment attributes) on spatial and temporal variabilities of individual flood event classes are explored using constrained rank analysis and a Monte Carlo permutation test. We identify five robust flood event classes, i.e., moderately, highly, and slightly fast floods as well as moderately and highly slow floods, which account for 24.0 %, 21.2 %, 25.9 %, 13.5 %, and 15.4 %, respectively, of the total number of events. All of the classes are evenly distributed in the entire period, but the spatial distributions are quite distinct. The fast flood classes are mainly in southern China, and the slow flood classes are mainly in northern China and the transition region between southern and northern China. The meteorological category plays a dominant role in flood event variabilities, followed by catchment attributes and land covers. Precipitation factors, such as volume and intensity, and the aridity index during the events are the significant control factors. Our study provides insights into flood event variabilities and aids in flood prediction and control.